IMPLEMENTATION OF SHARIA HEDGING TO MINIMIZE THE RISK OF FOREIGN EXCHANGE FLUCTUATIONS IN COMPANIES REGISTERED ON THE JAKARTA ISLAMIC INDEX (JII) - Sari, Eka Nurmala; Nurhayati, Nurhayati (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine and analyze the risk of foreign exchange losses faced by PT Astra Agro Lestari Tbk, PT AKR Corporindo Tbk, PT Astra Internasional Tbk, PT Perusahaan Gas Negara (Persero) Tbk, and PT Telekomunikasi Indonesia Tbk, as well as implementing forward contracts Sharia hedging so that risks can be minimized. This research uses a quantitative descriptive approach. The type of data used is secondary data using documentation methods from financial reports and annual reports of PT Astra Agro Lestari Tbk, PT AKR Corporindo Tbk, PT Astra Internasional Tbk, PT Perusahaan Gas Negara (Persero) Tbk, and PT Telekomunikasi Indonesia Tbk. The company chosen as the research object is a company registered with JII (Jakarta Islamic Index). The results of the research show that the application of sharia forward hedging contracts for net liabilities in foreign currency of PT Astra Agro Lestari Tbk, PT AKR Corporindo Tbk, PT Astra Internasional Tbk, PT Perusahaan Gas Negara (Persero) Tbk, and PT Telekomunikasi Indonesia Tbk can reduce the value foreign exchange losses during the year. The contract receivables account will increase the total asset balance while the contract payables account will increase the liabilities balance. Sharia forward hedging contracts can have a positive influence on companies which can be seen from changes that make financial reports better.